Stratified Soil Characterization using 1D Resistivity Inversion along the Pasuruan Coastline, East Java - Alam, Syaiful; Khoirullah, Nur; Rukmana, Yanwar Yusup (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
The inversion has been widely used in subsurface modeling of numerousdata. The number of stratified soil layer and thicknesswere driven by damped least-squares inversion method.This studyintegrated five borehole logs and six vertical electrical sounding measurements. The inversion result is able to predict an unsampled of borehole data. The resulting maximum rms error is 0.22 and minimum rms error is 0.011 from 1D inversion.The borehole datas indicatedgravelly soil layer, sandy soil layer,and clayey soil layer withthe resistivity values respectively range from 33.6-7.45 (Ohm.m), 7.45-3.98 (Ohm.m), and 3.98-0.016 (Ohm.m).Based on the studyresult there were possibilities of seawater intrusion indication according to the soil stratigraphic profile based on resistivity properties and borehole data. Keyword: Pasuruan coastline, stratified soil, 1D resistivity inversion.